Предмет: Алгебра,
автор: cthutqrkbvtyrj0
Решите уравнение(с объяснением), плз...
Приложения:
![](https://files.topotvet.com/i/81b/81b85b572e9b32f47a96a60394b915e9.jpg)
Ответы
Автор ответа:
1
!!!!!!!!!!!!!!!!!!!!!!!!!!!
Приложения:
![](https://files.topotvet.com/i/e17/e174c90201e7857627929be6b533d367.jpg)
cthutqrkbvtyrj0:
Спасибо
Автор ответа:
0
1) Разложим на множители знаменатель третьей дроби.
х² - 5х + 6 =
=х² - 3х - 2х +6 =
=(х² - 3х) - (2х - 6) =
= х(х-3) - 2(х-3) =
= (х-3)(х-2)
2)![\frac{x}{x-3} + \frac{3}{x-2} - \frac{3}{(x-3)(x-2)} =0 \frac{x}{x-3} + \frac{3}{x-2} - \frac{3}{(x-3)(x-2)} =0](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7Bx-3%7D+%2B+%5Cfrac%7B3%7D%7Bx-2%7D+-+%5Cfrac%7B3%7D%7B%28x-3%29%28x-2%29%7D+%3D0)
ОДЗ: х ≠2; х ≠ 3
х(х-2) + 3(х-3) - 3=0
х² - 2х + 3х - 9 - 3 = 0
х² + х - 12 = 0
D = b² - 4ac
D= 1 - 4·1·(-12) = 1+48=49
√D = √49 = 7
x₁ = (-1-7)/2 = -8/2 = - 4
x₂ = (-1+7)/2 = 6/2 = 3 - посторонний корень
Ответ: х = - 4
х² - 5х + 6 =
=х² - 3х - 2х +6 =
=(х² - 3х) - (2х - 6) =
= х(х-3) - 2(х-3) =
= (х-3)(х-2)
2)
ОДЗ: х ≠2; х ≠ 3
х(х-2) + 3(х-3) - 3=0
х² - 2х + 3х - 9 - 3 = 0
х² + х - 12 = 0
D = b² - 4ac
D= 1 - 4·1·(-12) = 1+48=49
√D = √49 = 7
x₁ = (-1-7)/2 = -8/2 = - 4
x₂ = (-1+7)/2 = 6/2 = 3 - посторонний корень
Ответ: х = - 4
Похожие вопросы
Предмет: Русский язык,
автор: dmitriy197rus
Предмет: Геометрия,
автор: kurinoyyaroslav
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: ИльяНабойченко